Strategic management : text and cases - Dess, Gregory G. (New York : McGraw Hill Education, 2010)
A fast, affordable and effective solution for all your course needs. The perfect resource for you and your instructor.
Strategic analysis -- Strategic formulation
Includes bibliographical references.
Keywords: PLANNING